The Postoperative Effects of Patellar Eversion in Total Knee Arthroplasty: An Updated Systematic Review and Meta-Analysis. (28th April 2022) - Wang, Jun; Guo, Jian-Bin; Wen, Peng-Fei; Zhang, Yu-Min; Song, Wei; Wang, Tao; Ma, Tao; Cheng, Qian-Yue; Zhang, Bin-Fei
Abstract : Background . During total knee arthroplasty (TKA), surgeons mobilize the patella to facilitate clear visualization of the articular surfaces and allow better prosthesis placement. According to the manipulation, this manipulation can be divided into patellar eversion and noneversion. However, the effect of patellar eversion in TKA is controversial, with substantial variability in clinical practice. This systematic review is aimed at assessing the adverse effects of patellar eversion and patellar noneversion duration in TKA. Methods . This updated systematic literature review identified randomized controlled trials comparing patellar eversion and noneversion durations in TKA. Two investigators independently extracted data and evaluated the quality of the studies. A meta-analysis was performed using RevMan version 5.3. Results . Nine studies with a total of 608 patients (730 knees) were included. Of these, 374 knees were classified in the eversion group and 356 knees in the noneversion group. The quality of the studies was high. The results showed that patellar eversion could increase the postoperative complication rate (relative   risk   RR = 1.67 ; 95% confidence interval [CI], 1.09–2.54; P = 0.02 ) and postoperative pain before discharge (mean   deviation   MD = 0.19 ; 95% CI, 0.04–0.34; P = 0.01 ), compared to noneversion. Additionally, patellar eversion could prolong the time until the patient is able to raise the leg while straightened (MD = 0.42 ; 95% CI, 0.24–0.59; P < 0.00001 ) and increase the length of stay (MD = 0.65 ; 95% CI, 0.05–1.25; P = 0.03 ). However, patellar eversion did not influence postoperative pain at 1 year (MD = 0.02 ; 95% CI, -0.23–0.28; P = 0.85 ), operative time (MD = − 2.66 ; 95% CI, -8.84–3.52; P = 0.40 ), recovery of quadriceps force throughout the follow-up period, and Insall–Salvati ratio (MD = − 0.04 ; 95% CI, [-0.11–0.02]; P = 0.23 ). Conclusions . The patellar eversion could increase the postoperative complication rate and postoperative pain. Current evidence supports the avoidance of patellar eversion in TKA. Further large-sample and long-term trials are required to validate these results.